The Effect of Binahong (Anredera cordifolia) 13% Leave Extract Gel on the Acceleration of Wound Healing Post Toot Extraction - Irfan Maulana Syam; Ari Suwondo; Endah Aryati Eko Ningtyas; Muhammad Saleh; Sainuddin Sainuddin; Awan Dramawan; Bahtiar Bahtiar (Alliance oh Health Activists (AloHA), 2024)
Tooth extraction is the act of removing a tooth from the socket in the alveolar bone. The wound healing process is divided into 4 continuous phases, namely hemostasis, inflammation, proliferation, and remodeling or maturation phases. Binahong leaf extract gel contains flavonoids, alkaloids, oleanolic acid, ascorbic acid, saponins and proteins used as antimicrobials. This study aims to determine that the binahong leaf extract gel has an effect on accelerating wound healing after tooth extraction. Binahong leaf extract gel was effective for accelerating wound healing after tooth extraction on the 10th day post test compared to the administration of povidone iodine, this was evidenced by the average inflammation control group of 0.81 seen from wound closure of 0.56 and the average intervention group seen from inflammation was 0.25 with p-value of 0.011 seen from wound closure of 0.13 with p-value of 0.010. As conclusion, giving binahong leaf extract gel 13% for 10 days has an effect on faster wound healing after tooth extraction compared to povidone iodine. Keywords: post-tooth extraction wounds; binahong leaf extract gel